Realization of Cultural Filter in The Indonesian – English Translation of “Gundala Movie” Subtitle - Putri, Widya Ivani (Universitas Negeri Semarang, 2021)
Translating a movie subtitle from Indonesian into English should be done carefully because Indonesian and English have some differences which may lead to ineffective communication, such as the changing of structures, the difference of meanings, and also dissimilarity of corresponding cultures. This phenomenon might be a concern since many Indonesian movies have entered international audiences and won some international awards, such as the Gundala movie that is directed by Joko Anwar. This study focused on analyzing the cultural filter implemented in Indonesian – English audio-visual translation of Gundala movie subtitles. The analysis utilizes the cultural filter theory proposed by House (2015). The data analysis focused in this study includes the characters’ utterances in Indonesian and its English subtitle provided in the Gundala movie. The subject is the Indonesian transcription from verbal dialogues produced by the movie characters in Gundala movie and its English subtitles shown on the screen. The object of the study is words, phrases, and sentences produced by the characters in the Gundala movie. Most translations applied cultural filter achieves functional equivalence. Theoretically, the cultural filter can help the translator to achieve functional equivalence. Practically, for the next translation project, it could be a good challenge for the next researcher to explore the translation studies using this theory. Pedagogically, the reader should be more familiar with the cultural differences between Indonesian and English.